THE ISSUE OF MEASUREMENT IN THE SERIES OF "YUSUF AND ZULAIKHO" SERIES - Rаxmonovа Shahnoza Muxitdinovna (Journals Park Publishing, 2024)
This article analyzes the issue of measurement in the series "Joseph and Zulayxo". For expressive reading of them, weight characteristics, measurement capabilities, coconuartic system have been studied. Instead, literature reacted to ideas.
Keywords: bees, weight, poetry, arrogant bahri, hazaj bahri, sari' bahri.